Developing Collaborative Governance Capabilities for Sustainable Development at Santer Application in Samarinda City (Universitas Terbuka, 2024)
Governments, development organizations, and others must increase their ability to tackle the complex difficulties of sustainable development. Significant investments in governance networks are being made by non-governmental groups. Nevertheless, excitement for there isn't always empirical support for the establishment of governance networks. This disparity presents difficulties. These groups to determine the value of their time and effort spent investing in governance networks; an assessment that is very important when resources are few. We assess the using a qualitative case study conducted in Samarinda City. proportionate share that the Santer Program, a governance network, made to four Individual, relational, organizational, and institutional are dimensions of collaborative governance capacity. We discover that the network contributed only moderately to the capacity of the individual, the relationship, and the organization, but the institutional capacity held steady in spite of the network's existence. This research is a qualitative study that will be conducted by reviewing the literature and examining the existing facts and data. Based on these findings, we argue that governance networks are not a panacea. Continued efforts are needed to establish when, how, and in what contexts collaborative networks are effective for building collaborative capacity for sustainable development. It would be fruitful for future studies to investigate how collaborative capacity changed over time, and in particular if increases in collaborative governance ability persisted after the network had stopped. Keywords: Collaborative Governance, Collaborative capacity, Samarinda City, Samarinda Santer